EKSPLORASI REFLEKTIF TEOLOGIS ATAS PERAN INJIL DALAM PROSES PERTUMBUHAN ROHANI BERDASARKAN KOLOSE 1:23 - Yuliantono Adi, Didit; Purwonugroho, Daniel Pesah (STT-RAI Batam, 2026)
This paper reflects theologically on the role of the gospel in spiritual growth based on Colossians 1:23. The gospel is the message that affirms God's work of salvation through Jesus Christ. The gospel details the life and person of Jesus Christ to bring salvation to all believers. Colossians 1:23 is a key text that crucially describes the perseverance of faith rooted in the Gospel. Colossians 1:23 affirms the superiority of Christ, which strengthens believers to continue to base their lives on the Gospel. Colossians 1:23 also emphasises the importance of perseverance in faith based on the Gospel as its core. Through a descriptive qualitative approach, the author attempts to explore the theological reflection of Colossians 1:23 on the role of the Gospel in the spiritual growth process of the congregation. The author asserts that the theological reflection of Colossians 1:23 emphasises the significant role of the Gospel in the spiritual growth process of the congregation. This paper offers a reflective-theological approach based on Colossians 1:23 to shape an understanding of the spiritual growth of the congregation based on the Gospel.